Faktor-Faktor yang Mempengaruhi Kemampuan Kognitif Lansia - Yuly Abdi Zainurridha; Nurcholisa Aulia Sakinah; Abdul Azis Azari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The most common cognitive dysfunction in the elderly is due to the effect on changes in emotions and behavior and the disruption of the elderly in carrying out daily activities independently, such as fulfilling nutrition, body hygiene and others. This literature review involved databases including Scopus, Science Direct, and Google Scholar using the keywords cognitive ability and the elderly, which resulted in 10 relevant articles. Based on the results of the review, there are several factors that affect the cognitive abilities of the elderly, including age, gender, education, occupation, nutritional status, heredity, and comorbidities, especially those that damage the nervous system such as dementia and Alzheimer's. An excellent strategy to improve the cognitive abilities of the elderly is cognitive stimulation such as fun activities that stimulate thinking, attention, and memory. Keywords: elderly; cognitive abilities; cognitive stimulation ABSTRAK Gangguan fungsi kognitif yang paling banyak terjadi pada lansia antara lain karena adanya efek terhadap perubahan emosi dan tingkah laku serta terganggunya lansia dalam melakukan aktivitas sehari-hari secara mandiri, seperti pemenuhan gizi, hygiene tubuh dan lain-lain. Literature review ini melibatkan database antara lain Scopus, Science Direct, dan Google Scholar dengan menggunakan kata kunci kemampuan kognitif dan lansia, yang akhirnya didapatkan 10 artikel yang relevan. Berdasarkan hasil review, ada beberapa faktor yang mempengaruhi kemampuan kognitif lansia antara lain usia, jenis kelamin, pendidikan, pekerjaan, status gizi, hereditas, dan penyakit penyerta, khususnya yang merusak sistem saraf seperti demensia dan alzheimer. Strategi yang sangat baik untuk meningkatkan kemampuan kognitif lansia adalah stimulasi kognitif seperti kegiatan menyenangkan yang merangsang pemikiran, perhatian, dan ingatan. Kata kunci: lansia; kemampuan kognitif; stimulasi kognitif